EFFECTS OF MURINE STRAIN, BLASTOCYST STAGE AND INNER CELL MASS ISOLATION TECHNIQUE ON THE EFFICACY OF MURINE EMBRYONIC STEM CELLS - Goh, S.Y.; Wan Khadijah, W.E; Abdullah, R.B (Malaysian Journal of Science, 2011)
The aim of this study was to compare the effects of murine strain, blastocyst stage and inner cell mass (ICM) isolation technique on the efficiency of deriving murine embryonic stem cell (mESC) lines. Foetal mouse embryonic fibroblasts (MEFs) were cultured to Passage 2, cryopreserved and thawed at each passage to be used as feeder layer for mESC culture. Five blastocyst stages from in vivo and in vitro produced blastocysts were cultured on the MEFs by using 3 different ICM isolation techniques. ICM outgrowths were disaggregated by trypsin/EDTA (0.05%) and manual dissociation, cultured on new inactivated MEFs in CO2 (5%) incubator, 37ÂºC. The attachment, primary ICM outgrowth and successful consecutive passages rates up to P3 were compared among the murine strains, blastocyst stages and ICM isolation techniques. There were significant differences (P<0.05) in successful passage rate at P3 between CBA/ca with ICR and C57BL/6J (19.81% vs. 9.00% and 8.50%), respectively, also mESC at P1 for mid-, expanded- and hatching blastocyst stages versus early- and hatched blastocyst (45.35%, 52.79% and 43.01% vs. 27.88% and 24.53%), respectively. Manual cut ICM isolation technique consistently gave the highest attachment, primary ICM outgrowth and successful mESC P2 and P3 rates compared with whole blastocyst culture and laser dissection techniques (78.03% vs. 66.52% and 71.06%; 78.35% vs. 75.32% and 75.67%; 52.06% vs. 41.62% and 45.06%; 36.52% vs. 25.77% and 30.49%), respectively. In conclusions, the CBA/ca strain, expanded blastocyst stage and manual cut ICM isolation techniques showed the highest results obtained in production of mESC lines. (Keywords: Blastocyst stage, ICM isolation technique, mESC, murine strain)